Fresh Fish Consumption in Semarang Indonesia - Poerwono, Dwisetia (1990)
In Indonesia, the present role of fish in the daily diet is very small. This study is aimed at determining the nature and causes of the 1011 consumption level of fish in Indonesia. Using cross section data of 179 sampled households and 65 fresh fishmongers in the public markets, the results of this study show that in the retail outlets of fresh fish the market is efficient. Both fishmongers and consumers (households) in majority indicated that fresh fish is readily available in the market. The largest number of households bought fresh fish regularly at least once a week. Milkfish, Mullet, Tilapia and Tuna are the species usually purchased. The major problem when buying fresh fish is freshness of fish.The acceptability of fresh fish varies among households, but in general, the relative acceptability index shows that chicken is preferred to fresh fish and beef, while milkfish is preferred to other fish and beef. Two models have been used in this study for estimating the parameters of the fresh fish demand system. First, logarithmic linear functions of demand system model-using OLS and second, Zellner's Seemingly Unrelated Regression (SUR) model. The logarithmic linear function of demand system of fresh fish used in this study looks appropriate for estimating the demand for fresh fish. The symmetry restriction on this demand function is accepted. The Goldfeld-Quandt test applied to the data indicates heteroscedasticity is not a problem in this logarithmic demand system. Meanwhile Zellner' s Seemingly Unrelated Regression (SUR) yield estimates which are asymptotically more efficient than those obtained by Ordinary Least Squares (OLS). So, the Seemingly Unrelated Regression have been applied in this study for estimating the demand function of fresh fish. With the exception of Tilapia, the findings of this study show that the demand for fresh fish is elastic with respect to its own price. The coefficient of own price elasticities ranged from -0.6756 to -2.2591. While the expenditure elasticities are positive and significantly different from zero except for Mullet. Based on the results of this study, consumption of fresh fish can be enhanced if the following actions are also taken: improvement of the fish stall in public markets, promotion of fish consumption, provision of government subsidies on fuel for fishermen, provision of subsidies on fertilizer, pesticides and low interest credit scheme far fish farmers.